Changes in Physical Activity After Total Hip or Knee Arthroplasty: A Systematic Review and Meta‐Analysis of Six‐ and Twelve‐Month Outcomes. Issue 6 (16th April 2018) - Hammett, Thomas; Simonian, Aram; Austin, Monica; Butler, Robert; Allen, Kelli D.; Ledbetter, Leila; Goode, Adam P.
Abstract : Objective: Little is known about the extent to which physical activity (PA) levels change following total knee or hip joint replacement relative to pain, physical function, and quality of life. Our objective was to conduct a systematic review and meta‐analysis on changes in PA relative to pain, quality of life, and physical function after total knee or hip joint replacement. Methods: We searched the PubMed (Medline), Embase, and CINAHL databases for peer‐reviewed, English‐language cohort studies measuring PA with an accelerometer from presurgery to postsurgery. Random‐effects models were used to produce standardized mean differences (SMDs) for PA, quality of life, pain, and physical function outcomes. Heterogeneity was assessed using I 2 . Results: Seven studies (336 participants) met the eligibility criteria. No significant increase in PA was found at 6 months (SMD 0.14 [95% confidence interval (95% CI) −0.05, 0.34]; I 2 = 0%) and a small to moderately significant effect was found for increasing PA at 12 months (SMD 0.43 [95% CI 0.22, 0.64]; I 2 = 0%). Large improvements were found at 6 months in physical function (SMD 0.97 [95% CI 0.12, 1.82]; I 2 = 92.3%), pain (SMD −1.47 [95% CI −2.28, −0.65]; I 2 = 91.6%), and quality of life (SMD 1.02 [95% CI 0.30, 1.74]; I 2 = 83.2%). Conclusion: Physical activity did not change at 6 months, and a small to moderate improvement was found at 12 months postsurgery, despite large improvements in quality of life, pain, and physical function. Reasons for the lack of increased PA are unknown but may be behavioral in nature, as a sedentary lifestyle is difficult to change. Changing sedentary behavior should be a future focus of research in this subgroup.